2022
DOI: 10.1002/nafm.10830
|View full text |Cite
|
Sign up to set email alerts
|

Big Catch, Undecided Risks: Perspectives of Risk, Reward, and Trade‐Offs in Alaska's Salmon Enhancement Program

Abstract: Alaska's salmon enhancement program plays an important and substantial role in commercial fishing harvests situated around the Gulf of Alaska, Prince William Sound, and Southeast Alaska. In recent years, discussions about the ecological impacts of the enhancement program have emerged in the media, the Alaska Board of Fisheries, and other public discourses. These discussions have illuminated tension within Alaskan society about the role and impacts of hatcheries in fisheries and coastal communities. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
5
0
1
Order By: Relevance
“…Furthermore, the authors found those who oppose hatcheries express concerns about hatchery water use and the contribution of hatchery fish towards exacerbating other climate stressors, including dissolved oxygen depletion (ibid). Whereas in previous research scientific complexity over climate phenomena was dismissed by fishers in favor of existing mental schemas for attribution, in comments to the Board and other fisheries discourse in Alaska (Harrison and Gould, 2022), divergent science on interactions of wild and hatchery salmon seems to feed entrenched viewpoints largely defined by those who do and do not directly benefit from hatchery production.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the authors found those who oppose hatcheries express concerns about hatchery water use and the contribution of hatchery fish towards exacerbating other climate stressors, including dissolved oxygen depletion (ibid). Whereas in previous research scientific complexity over climate phenomena was dismissed by fishers in favor of existing mental schemas for attribution, in comments to the Board and other fisheries discourse in Alaska (Harrison and Gould, 2022), divergent science on interactions of wild and hatchery salmon seems to feed entrenched viewpoints largely defined by those who do and do not directly benefit from hatchery production.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Harrison and Gould (2022) examined public comments to a 2019 Board meeting on hatcheries coupled with semi-structured interviews with fisheries stakeholders to identify the themes that underlie tensions over hatcheries in Alaska -the results of which illuminate hatchery discourse in our analysis and are discussed further below. Our analysis contributes to this growing body of literature on public participation processes in Alaska fisheries through the use of big qualitative data methods to examine the full corpus of publicly available, digitized comments to the Board.…”
Section: The Gulf Of Alaska Fisheries Systemmentioning
confidence: 99%
“…Where conservation work is undertaken by communities, hatcheries facilitate social and psychological benefits to those participating in stocking (i.e. habitat improvement work from hatchery volunteers) (Harrison, Kochalski, et al., 2018), act as locations where scientific and local knowledge may be used and hybridized together for conservation purposes (Harrison, Rybraten, & Aas, 2018), and can provide local employment opportunities (Amberson et al., 2016; Harrison & Gould, 2022).…”
Section: Conservation For Who When and Why?mentioning
confidence: 99%
“…As such, scholars can offer a PubCast option to the publisher upon receiving proofs or submitting final drafts of work. Ideally, the publisher will embed the recording link directly into the manuscript (see example Harrison & Gould, 2022).…”
Section: A Means Of Hosting and Distribution (Such As Researchequals ...mentioning
confidence: 99%